Dinamika Literasi Digital Generasi X di Pedesaan dalam Proses Seleksi Kerja Publik melalui Aplikasi Online: Studi di Kabupaten Abdya - Aria Ningsih, Rahma; Basri, Hasan; Taufik, Muhammad (Da'watuna: Journal of Communication and Islamic Broadcasting, 2026)
This study aims to analyze the dynamics of digital literacy among Generation X in the public job selection process through online applications in Pante Rakyat Village, Babahrot District, Southwest Aceh Regency. This study focuses on understanding the abilities, experiences, and obstacles faced by Generation X in adapting to digital systems used in public recruitment and administrative services. A descriptive qualitative method was applied with data collected through in-depth interviews involving ten informants categorized as Generation X (born between 1964 and 1980). The findings revealed that most participants have digital devices and adequate internet access, yet they still struggle with technical skills such as account creation, uploading documents, and understanding online instructions. Age, low self-confidence, and lack of training were identified as the main barriers to digital adaptation. However, social support from family and community played a significant role in assisting them during the online selection process. This study concludes that improving Generation X's digital literacy requires educational approaches and practical mentoring to enable their independent participation in digital-based public recruitment systems.